The Archaeology of Rock Art in Western Arnhem Land, Australia (Terra Australis 47) - David, Bruno; Tacon, Paul; Delannoy, Jean-Jaques; Geneste, Jean-Michel (ANU Press, 2018)
Western Arnhem Land, in the Top End of Australia's Northern Territory, has a rich archaeological landscape, ethnographic record and body of rock art that displays an astonishing array of imagery on shelter walls and ceilings. While the archaeology goes back to the earliest period of Aboriginal occupation of the continent, the rock art represents some of the richest, most diverse and visually most impressive regional assemblages anywhere in the world. To better understand this multi-dimensional cultural record, The Archaeology of Rock Art in Western Arnhem Land, Australia focuses on the nature and antiquity of the region's rock art as revealed by archaeological surveys and excavations, and the application of novel analytical methods. This volume also presents new findings by which to rethink how Aboriginal peoples have socially engaged in and with places across western Arnhem Land, from the north to the south, from the plains to the spectacular rocky landscapes of the plateau. The dynamic nature of Arnhem Land rock art is explored and articulated in innovative ways that shed new light on the region's deep time Aboriginal history.